Training the University professor from a human dimension - Carmen Niurka Piña Loyola; Aimeé Seife Echevarría; Aida María Díaz Pérez; Petrona Pez Camerón; Katia Rodríguez Palacios (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
In the present society it is required professionals with high critical and ethical sense, with a social humanistic scientific and technical training, able to respond the increasing demands they shall need to solve in their professional lives as citizens and human beings. A professional trained from a humane dimension is coherent in his values, understands his role in the society, in the family in his community and is someone in constant development. The purpose of this article is to provide a theoretical and reflexive compilation about the need of training a university professor to meet the needs of the current society, so as to share the concerns and hopes that the educative task arises in all those who participate in it.